Analisis Kemampuan Computational Thinking Dalam Pembuatan Media Pembelajaran Matematika - Rizal Dian Azmi; Siti Khoiruli Ummah (Jurnal Pendidikan Matematika:Judika Education, 2021)
The purpose of this study was to reveal the implementation of Project Base Learning (PjBL)-based learning and then analyze the Computational Thinking (CT) ability of students of the Mathematics Education Study Program, University of Muhammadiyah Malang through a learning media development project. The approach used in this research is descriptive qualitative. The subjects in this study were students who programmed the Programming Language course in semester 3. The results of the research, the projects carried out in PjBL learning were making learning media using Matlab which included the stages of needs analysis, project planning, scheduling, monitoring, testing results and evaluating carried out. very well and systematically. The media produced by students has met the aspects of fluency in use, accuracy of scripts, and flowchart logic. The student's CT ability is in a good category from the aspect of abstraction, logarithmic thinking, debugging/evaluation, and generalization because it has met the achievement percentage of 82%. In conclusion, the learning media developed based on Project Base Learning (PjBL) has been implemented well, covering aspects of smooth use and effectively increasing the Computational Thinking (CT) ability of students of the Mathematics Education Study Program, University of Muhammadiyah Malang. Keywords: Computational Thinking, Learning Media, Project Base Learning